Enhanced remyelination following lysolecithin-induced demyelination in mice under treatment with fingolimod (FTY720). (17th December 2015) - Yazdi, A.; Baharvand, H.; Javan, M.
Graphical abstract: Highlights: FTY720 reduced the severity of inflammation at lysolecithin-induced lesion. FTY720 enhanced remyelination in animals challenged with local lysolecithin. FTY720 increased the number of newly produced oligodendrocyte lineage cells and remyelinated axons. Abstract: Multiple sclerosis (MS) is a chronic, progressive demyelinating disorder which affects the central nervous system (CNS) and is recognized as the major cause of nervous system disability in young adults. Enhancing myelin repair by stimulating endogenous progenitors is a main goal in efforts for MS treatment. Fingolimod (FTY720) which is administrated as an oral medicine for relapsing-remitting MS has direct effects on neural cells. In this study, we hypothesized if daily treatment with FTY720 enhances endogenous myelin repair in a model of local demyelination induced by lysolecithin (LPC). We examined the response of inflammatory cells as well as resident OPCs and evaluated the number of newly produced myelinating cells in animals which were under daily treatment with FTY720. FTY720 at doses 0.3 and 1 mg/kg decreased the inflammation score at the site of LPC injection and decreased the extent of demyelination. FTY720 especially at the lower dose increased the number of remyelinated axons and newly produced myelinating cells. These data indicate that repetitive treatment with FTY720, behind an anti-inflammatory effect, exerts beneficial effects on the process of endogenous repair of demyelinating insults.